Doing discourse research : an introduction for social scientists - Keller, Reiner , 1962- (SAGE, 2013)
This book provides an introduction to the basic principles of discourse research, offering practical research strategies for doing discourse analyses in the social sciences. The book includes guidance on developing a research question, selecting data and analyzing it, and presenting the results. The author has extensive practical experience in the field of discourse research and shows, throughout, how the methods suggested are compatible with numerous research questions and problems in sociology, cultural, political and social studies